Highly Asymmetric n+–p Heterojunction Quantum‐Dot Solar Cells with Significantly Improved Charge‐Collection Efficiencies. Issue 9 (21st December 2015) - Choi, Min‐Jae; Kim, Sunchuel; Lim, Hunhee; Choi, Jaesuk; Sim, Dong Min; Yim, Soonmin; Ahn, Byung Tae; Kim, Jin Young; Jung, Yeon Sik
Abstract : The depletion region width of metal‐oxide/quantum‐dot (QD) heterojunction solar cells is increased by a new method in which heavily boron‐doped n + ‐ZnO is employed. It is effectively increased in the QD layer by 30% compared to the counterpart with conventional n‐ZnO, and provides 41% and 37% improvement of J sc (16.7 mA cm −2 to 23.5 mA cm −2 ) and power conversion efficiency (5.52% to 7.55%), respectively.